El canto popular entre política y religión: la visión de Mário de Andrade - Enea Zaramella (Brasiliana: Journal for Brazilian Studies, 2015)
Mário de Andrade identifies rhythm as the common structural underpinning between poetry and song. Rhythm is also the apple of discord between them, since it is with rhythm that we are able to note the fundamental distinction between the sung and the spoken word. As well as differentiating language by means of its use, popular song also fluctuates rhythmically; that is, it has another ‘wave’ (or mood) which varies depending on a series of other factors, which Andrade calls to mind. By considering 'canto' (chant) in psycho-physical terms, this essay offers an interpretation of Andrade’s reading of the masses present at one political event in 1930 described in “Dinamogenias políticas.” Moreover, this paper connects the political with the religious practices introduced in Brazil by the Jesuits, focusing above all on the Gregorian chant. I propose that with his “Crítica do gregoriano” Andrade offers a counterpoint by which to understand popular music in Brazil.